Ensuring adhesion between the asphalt-concrete road surface and rigid base at the roadbed design stage - Dorozhko, Yevhen; Batrakova, Angelika; Tymoshevskyi, Vladislav; Zakharova, Elina (Eastern-European Journal of Enterprise Technologies, 2021)
Arranging asphalt-concrete layers on a rigid base in the form of cement-concrete slabs can significantly improve the transporting and operational performance of the road surface. Such a structural solution is appropriate in almost all countries of the world since cement-concrete slabs retain high strength for a long time. To prevent the rapid destruction of an asphalt-concrete road surface on a rigid base, it is necessary to ensure reliable adhesion between the layers' contacts and, at the design stage, to test the adhesion strength by estimation. This paper has substantiated a criterion of adhesion strength in the contact between an asphalt-concrete road surface and the rigid base. The calculation involves comparing the active tangent stresses in the contact between layers dependent on the effect of the vertical and horizontal components of the transport load with the magnitude of permissible tangent shear stresses in the contact of layers. The parameters for an estimation model have been established; the stressed-strained state of the roadbed structure has been simulated using a finite element method. When modeling the stressed-strained state and calculating based on the strength criterion, different vehicle traffic conditions have been considered, as well as the effect of temperature on the strength parameters of the asphalt-concrete layer and the tar layer. The conditions for vehicle movement, taken into consideration when designing, correspond to the conditions of movement along the road, along the curves in the plan and profiles, and notion conditions at car emergency braking. Practical recommendations have been compiled for assigning the minimum permissible thickness of an asphalt-concrete layer on a rigid base, which must be followed at the design stage due to the condition for ensuring reliable adhesion between the layers' contacts. The minimum permissible thickness ranges from 2 cm to 10 cm, depending on the conditions of movement, temperature, and the type of tar.